A designer bow-tie combination therapeutic platform: An approach to resistant cancer treatment by simultaneous delivery of cytotoxic and anti-inflammatory agents and radiation. (December 2018) - Pathak, Rakesh K.; Basu, Uttara; Ahmad, Anis; Sarkar, Shrita; Kumar, Anil; Surnar, Bapurao; Ansari, Saba; Wilczek, Katarzyna; Ivan, Michael E.; Marples, Brian; Kolishetti, Nagesh; Dhar, Shanta
Abstract: Multimodal therapies are used to treat advanced cancers including castration-resistant prostate cancer to manage the biological characteristics of the tumors like inflammation, bone metastases, and participation of metabolically altered cancer stem cells (CSCs) that have integral roles in disease dissemination and progression. We developed a multifunctional polymer-based self-assembled technology to deliver a predefined stoichiometric combination of a chemotherapy and an anti-inflammatory agent in a stimuli responsive manner, to complement and improve the currently established treatment methods of prostate cancer. We combined clinically applicable fractionated radiation therapy (XRT) to further sensitize the activity of this targeted multifunctional platform towards prostate-specific membrane antigen (PSMA) expressing advanced prostate cancer. After irradiation, our PSMA-targeted self-assembly system could modulate the mitochondrial metabolism, cellular respiration and the overall radiation-induced DNA damage process. We report the synthesis of this advanced multifunctional platform and describe its unique properties that allow the ability to load multiple FDA approved drugs with a predefined stoichiometric ratio for targeted co-delivery of chemotherapeutics and anti-inflammatory agents. The efficacy of this platform was demonstrated using several in vitro and in vivo studies, in a unique bilateral PSMA expressing prostate cancer tumor model, and in patient derived CSCs.